A Memória rema contra a maré : lembranças sobre a degradação ambiental da Praia do Aracaju - Lima, Luis Eduardo Pina (2013)
The present research has for object the construction of memories of people living near the edge of the Industrial neighborhood, in the city of Aracaju, related to the way in which they perceive and ascribe meaning to the environmental degradation of the existing on-site small beach. Working with the basic assumption that memory re-making experience in relation to the environment inhabited (Bergson, 2006). For both, it was established that the general objective of this research is to analyze how those memories re-makes through the oral accounts collected based on phenomenology and through thematic oral history methodology. This is an exploratory research, interdisciplinary character, with an intentional sampling of 10 subjects over the age of 60 years, who live more than 30 years in that place. It was noticed that the subjects involved in this research they rebuilt their experiences regarding environmental degradation of Industrial neighborhood.s small beach, based on the strength of his memoirs.